2012
DOI: 10.1158/2159-8290.cd-11-0284
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Glioma- versus Lung Cancer–Specific EGFR Mutations to EGFR Kinase Inhibitors

Abstract: Activation of the epidermal growth factor receptor (EGFR) in glioblastoma (GBM) occurs through mutations or deletions in the extracellular (EC) domain. Unlike lung cancers with EGFR kinase domain (KD) mutations, GBMs respond poorly to the EGFR inhibitor erlotinib. Using RNAi, we show that GBM cells carrying EGFR EC mutations display EGFR addiction. In contrast to KD mutants found in lung cancer, glioma-specific EGFR EC mutants are poorly inhibited by EGFR inhibitors that target the active kinase conformation (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
278
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(294 citation statements)
references
References 46 publications
7
278
1
Order By: Relevance
“…Those discouraging results 62,63 probably explain why the usual dose is inadequate in the clinical setting. Vivanco et al 64 showed that the most frequent mutation of EGFR in gbm is relatively insensitive to erlotinib, being more sensitive to other egfr inhibitors (for example, HKI-272 or lapatinib).…”
Section: Inhibitors Of Egfr: Monotherapy or Combination?mentioning
confidence: 99%
“…Those discouraging results 62,63 probably explain why the usual dose is inadequate in the clinical setting. Vivanco et al 64 showed that the most frequent mutation of EGFR in gbm is relatively insensitive to erlotinib, being more sensitive to other egfr inhibitors (for example, HKI-272 or lapatinib).…”
Section: Inhibitors Of Egfr: Monotherapy or Combination?mentioning
confidence: 99%
“…However, the use of HER1/EGFR inhibitors targeting the inactive conformation of the receptor should be regarded with caution. So far, two clinical studies have failed to show a clinical benefit of lapatinib in the setting of recurrent glioblastoma (38,40). These results may be partly explained by the fact that mean tumor tissue concentrations of lapatinib were more than 10 times lower than those reported for erlotinib, which has a molecular size that is approximately half of that of lapatinib (38,41).…”
Section: U87mgmentioning
confidence: 98%
“…This finding is of particular interest because recently, two studies addressed the question why non-small cell lung cancer (NSCLC) and glioblastoma respond differently toward HER1/EGFR-targeted agents (38,39). Vivanco and colleagues showed that glioblastoma cell lines carrying glioblastoma-specific HER1/EGFR mutations were responsive toward an HER1/EGFR inhibitor directed against the inactive conformation of the catalytic tyrosine kinase domain, that is, lapatinib, an observation that contrasts with the findings in NSCLC cell lines (38). The authors concluded that the clinical failure of first-generation HER1/EGFR inhibitors in glioblastoma may be due to differences among NSCLC and glioblastoma in the conformational state of the receptor that is required for efficient inhibition.…”
Section: U87mgmentioning
confidence: 99%
See 1 more Smart Citation
“…These are due to the compensatory mechanisms of alternative signaling pathways and cellular heterogeneity of glioblastoma as well as the insufficient penetration of drugs across the blood-brain barrier [215]. It is necessary to find another strategy that targets multiple genes simultaneously.…”
Section: Introductionmentioning
confidence: 99%